159 The Role of Proformas in Improving the Documentation of Surgical Ward Rounds. (28th February 2022) - Coyle, M.; McManaman, C.; Smith, B.
Abstract: Introduction: Several NHS trusts rely on handwritten notes, including ward round (WR) reviews. These are essential in-patient care and must be completed/documented thoroughly. The General Medical Council and Royal College of Surgeons have both published guidance on WR documentation. Method: This was a prospective study aiming to review WR documentation within general surgery at Frimley Park Hospital. 17 WR entries were reviewed using an 18-point checklist. A proforma was created based on published guidance and gaps in reviewed documentation. This was introduced for two months before a repeat review was conducted. A third review was conducted after an additional month to monitor for sustained improvement. Results: Strengths in the baseline included documentation of WR leads (100%) and plans (100%), legible handwriting (95%), and NEWS score (88%). Common weaknesses were documentation of full observations, anticoagulation (both 6%), and relevant bloods and imaging (both 12%). The two months post-proforma review found improvement in all 18 areas of documentation, with five elements scoring 100%. Documentation of anticoagulation improved from 6% to 94%, relevant bloods from 12% to 82%, and full observations from 6% to 76%. Higher scoring WRs were linked to pre-prepared proformas, with lower scores linked to post-take WRs. The review was repeated after an additional month, showing consistently improved results in all areas. Conclusions: This project has shown significant and sustainable improvement in WR documentation with the proforma. This project would therefore recommend the continued use of the proforma, and an additional review after the junior doctor change over to show continued sustainability.